2015
DOI: 10.1016/j.jneuroim.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic syndrome-associated neuronal antibodies in adult ADHD

Abstract: A high seroprevalence of Yo antibodies targeting cerebellar Purkinje cells was recently reported in children with attention deficit/hyperactivity disorder (ADHD). We investigated the presence of 8 paraneoplastic neurological syndrome (PNS)-associated antibodies including anti-Yo in 169 adult ADHD patients. No associations between ADHD and serum Yo antibodies or other antibodies associated with PNS were found. However, 10 out of 48 ADHD patient sera analyzed by immunofluorescence presented antibodies targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…; 4024Amph, Ma1, Ma2, CRMP-5/CV2, Tr, Hu, Rec, Ri, YoIIFDSM-IV100%/100%-Moon et al 2014 [47]South Korea– 12-14S (r)Non-stiff amphiphysin syndrome20/207/2058*; 4012Amph., Hu, Yo, Ri, Ma2, CRMP-5.Im.bl.None25%/25%Irritability, psychosisLaadhar et al 2015 [17]Tunisia -?S (c)Psychiatric patHealthy controls5/1030/410/1030/4143*; 2841*; 22ANNA, PCA1, ANAHu, Ri, YoWB, IIFDSM-IV100%/100%Schizophrenia, schizoaff. And bipolar disord.Haukanes et al 2015 [43]Norway -?S (c)ADHD patHealthy controls0/1690/560/1690/5633*; 5035*; 55Yo, Amph, CRMP-5, Ma2, Ri, HuYo, Amph, CRMP-5/CV2, Ma2, Ri, HuIm.bl, WB, IIFDSM-IV100%/−-Kruse et al 2015 [44]US (Roch)- 02–11S (r)Psychiatric inpatHealthy controls1/2130/173?? ;??Hu, Ri, SOX1, Yo, CRMP-5/CV2, Amph, TrIm.bl, IIF, ELISAChart review100%/100%Pers ch, paranoia, agitation etcEndres et al 2015 [42]Germany – 06-13S (c)Pat with psychotic synd.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…; 4024Amph, Ma1, Ma2, CRMP-5/CV2, Tr, Hu, Rec, Ri, YoIIFDSM-IV100%/100%-Moon et al 2014 [47]South Korea– 12-14S (r)Non-stiff amphiphysin syndrome20/207/2058*; 4012Amph., Hu, Yo, Ri, Ma2, CRMP-5.Im.bl.None25%/25%Irritability, psychosisLaadhar et al 2015 [17]Tunisia -?S (c)Psychiatric patHealthy controls5/1030/410/1030/4143*; 2841*; 22ANNA, PCA1, ANAHu, Ri, YoWB, IIFDSM-IV100%/100%Schizophrenia, schizoaff. And bipolar disord.Haukanes et al 2015 [43]Norway -?S (c)ADHD patHealthy controls0/1690/560/1690/5633*; 5035*; 55Yo, Amph, CRMP-5, Ma2, Ri, HuYo, Amph, CRMP-5/CV2, Ma2, Ri, HuIm.bl, WB, IIFDSM-IV100%/−-Kruse et al 2015 [44]US (Roch)- 02–11S (r)Psychiatric inpatHealthy controls1/2130/173?? ;??Hu, Ri, SOX1, Yo, CRMP-5/CV2, Amph, TrIm.bl, IIF, ELISAChart review100%/100%Pers ch, paranoia, agitation etcEndres et al 2015 [42]Germany – 06-13S (c)Pat with psychotic synd.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 27 original publications that met eligibility criteria [2, 17, 2549]. Data about the serum prevalence of well-characterized onconeural antibodies in patients with psychiatric disorders were available from 6 papers [17, 29, 41, 43, 44, 46]. Authors of 1 paper reported on the prevalence of anti-Purkinje cell antibodies “similar to those found in paraneoplastic cerebellar degeneration”, but did not specify if tests for well-characterized onconeural antibodies were performed [39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations